Landscape of paediatric pain in Sub-Saharan Africa: a scoping review - Rebecca Gray; Salome Maswime; Romy Parker; Raymond Ndikontar; Anisa Bhettay; Kotie Bester; Kim MacQuilkan (BMJ Public Health, 2025)
Introduction Pain is impacted by various biopsychosocial factors, including context and culture. Children in Sub-Saharan Africa present with unique diseases with a high pain burden. Robust scientific research on paediatric pain in Sub-Saharan Africa is lacking.Methods A scoping review was conducted to describe the pain prevalence, pain management practices and health system factors impacting pain management and to map the relevant research landscape in sub-Saharan Africa. The search strategy combined pain, location and age-related terms. Studies from 2000 to 2022 from countries in Sub-Saharan Africa pertaining to acute, procedural and chronic pain in children from birth to 18 years were included. Searches were conducted in African-Wide EBSCO, CINAHL, Epistemonikos, PubMed, Scopus, Web of Science, Scielo and the Cochrane Library. A thematic approach was applied for data synthesis through an iterative process, and results presented narratively.Results After applying eligibility criteria, 68 studies were included. Studies demonstrated a high prevalence of acute and procedural pain in hospitalised children, with neonates a particularly vulnerable group. While various tools were validated for local populations, evidence-based pain assessment and management was lacking. Demonstrated knowledge deficits among healthcare workers translated into inadequate pain management. Utilisation of non-pharmacological strategies was varied. Resource limitations pose substantial obstacles to effective pain control. Data on chronic pain remains scant.Conclusion This review presents a comprehensive synthesis of the evidence on paediatric pain management in Sub-Saharan Africa. It highlights the need to direct resources towards addressing deficits in paediatric pain management. Training of healthcare providers and developing evidence-based guidelines is imperative. Robust research on paediatric pain in Sub-Saharan Africa is needed to inform targeted interventions to improve pain management, reducing the pain burden in children in the region.